Emergence of an optrA-positive Enterococcus faecalis ST699 lineage in animal-derived foods in Beijing, China - Chuncai Liang; Yizhu Chen; Xuan Wu; Rui Chang; Wenkai Cao; Ling Wei; Hui Li; Bing Shao (International Journal of Food Microbiology, 2026)

Correction: Cell-free mitochondrial DNA as a potential predictor for hypoxic stress - Qiaoping Qu; Can Xiao; Xuemei Liu; Aixue Huang; Hui Li; Gang Xu; Ningsheng Shao; Yuechao Zhao; Bo Gao (Molecular Biology Reports, 2026)

Cell-free mitochondrial DNA as a potential predictor for hypoxic stress - Qiaoping Qu; Can Xiao; Xuemei Liu; Aixue Huang; Hui Li; Gang Xu; Ningsheng Shao; Yuechao Zhao; Bo Gao (Molecular Biology Reports, 2026)

Bubble-enhanced micromixing in an enzyme/MnO2 system immobilized in a covalent organic framework for boosting enzymatic catalysis - Zheng-Feng Zhang; Jia-Yi Shao; Hui-Ting Li; Xiao-Hui Yao; Wei-Guo Zhao; Xin Chen; Dong-Yang Zhang (Sustainable Chemistry and Pharmacy, 2026)

Dry mafic recharge modulates degassing in rift-related magma reservoirs recorded by a giant porphyry Mo system - Wen-Tian Li; Shao-Yong Jiang; M. Wiedenbeck; Hao-Xiang Zhang; Yan-Liang Yin; Hui-Min Su (Earth and Planetary Science Letters, 2026)

Integrated interfacial regulation enables stable ampere-level alkaline hydrogen evolution - Qianwei Chen; Li Ma; Xingyu Bai; Jieyu Zhang; Dongyu Wang; Ke Ning; Yanmou Shao; Hui Chai; Shu-Juan Bao; Longcheng Zhang (Chemical Engineering Journal, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Analytical and Numerical Evaluation of the Lateral Dynamic Response of Piles at Slope Crests - Shao Yue; Hui Weng; Wenzhe Peng; Chenchen Li; Bing Duan; Shengnan Li (Geotechnical and Geological Engineering, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Resilient bioconversion of nitrite-rich organic wastes by black soldier fly larvae: Detoxification mechanisms and microbiome-mediated nitrogen cycling - Chaowei Qin; Mengjun Long; Jiabao Chen; Dan Shao; Shanshan Zhao; Long Chen; Zhenyu Zhang; Lijun Duan; Huan He; Juan Cortes Ortiz; Hui Wei; Qing Li; et al. (International Biodeterioration & Biodegradation, 2026)

Late Triassic Magmatic-Hydrothermal Origin of the Jiangfeng Fe-Co Deposit (Yunnan, SW China): Constraints from Titanite U-Pb Dating and Sulfur Isotopes - Hui-Min Su; Shao-Yong Jiang; Shufu Chen; Xianda Jiang; Guolong Zheng; Xiayu Li (Journal of Earth Science, 2026)

Pan-cancer characterization of the pyrimidine catabolic enzyme UPB1 identifies a tumor-suppressive prognostic biomarker in skin cutaneous melanoma - Yingli Men; Yi Shao; Yongfeng Chen; Ping Wang; Yiyang Li; Zhenzhen Yang; Ruiting Feng; Hui Wang; Yinsen Song; Cong Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A hybrid mantle source for Chang’E-5 basalt: insights from ultra-trace element ratios of olivine - Cheng-Yu Du; Shao-Bing Zhang; Hejiu Hui; Ting Liang; Wan-Cai Li; Yong-Fei Zheng (Geochimica et Cosmochimica Acta, 2026)

Plate bridge damage identification based on contact point response of vehicle-bridge system - Wen-Yu He; Jin-Tong Su; Yong-An Wang; Ya-Hui Shao; Dan Li (Engineering Structures, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Structural characterization and antitumor activity via immune modulation of an α-glucan from Grifola frondosa - Hui-Xiang Tian; Qin-Zhao Ruan; Yi-Zhen Xie; Wei Chen; Chun Xiao; Wei Zhong; Yuan-Chao Liu; Shao-Dan Chen; Tian-Qiao Yong; Hui-Ping Hu; Xiang-Min Li; Qing-Ping Wu (Carbohydrate Polymers, 2026)

CM-TRAP: A chemoproteomic workflow for profiling circulating metabolites and their protein targets in Alzheimer's disease - Xinmiao Wang; Xiangyu He; Xiaoyu Pu; Xingchao Yang; Yi Li; Hanqing Zhang; Haiping Hao; Chang Shao; Hui Ye (Analytica Chimica Acta, 2026)

New cutting tool wear testing method for evaluating the influence of foam additive on plowing effect during shield TBM tunnelling in dense sandy gravel ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Yu-Cong Pan; Wei-Qiang Xie; Xin-Fang Li; Hao-Jie Wang (Tunnelling and Underground Space Technology, 2026)

Integrated metabolomic and genomic profiling reveals Bacillus cereus-mediated degradation pathways for Glufosinate-ammonium - Yi Gu; Xiaoqing Li; Xiaolan Shao; Menglong Li; Hui Li; Liangyu Chen; Yiping Jiang; Kailin Liu; Bei Yan (Pesticide Biochemistry and Physiology, 2026)

Dynamic response and stability analysis of subsurface structures in porous coral reefs under coupled seismic-hydrodynamic conditions - Tingting Liu; Xiaohan Xie; Luyang Ding; Yiqiang Shao; Hui Shen; Xinping Li; Shenghao Yang (Ocean Engineering, 2026)

Structural dynamics of chloroplast genome in Paphiopedilum (Orchidaceae): in response to natural hybridization - Xue-Ying Wei; Ai-Qun Hu; Jin Zhou; Jiang-Ping Shu; Wei-Yue Sun; Li-Qiang Li; Jian-Wen Shao; Hui Wang; Yue-Hong Yan (Molecular Phylogenetics and Evolution, 2026)

Targeting STING activation in antigen-presenting cells via natural polysaccharide-engineered vesicles for antitumor immunotherapy - Tian-Yang Wang; Lang Zhao; Geng-Hui Feng; Jing-Yun Su; Shao-Hua Zhuo; Yan-Mei Li (Chemical Engineering Journal, 2026)

Grazing Stocking Rate and Rainfall Jointly Regulate Soil Methane Uptake in a Temperate Meadow Steppe, but Do Not Reverse Net Methane Emissions - Tianqi Yu; Yu Zhang; Miao Wang; Chu Zhang; Jiquan Chen; Yuchun Yan; Xu Wang; Changliang Shao; Xiaotao Lü; Hui Li; Linghao Li; Lianhai Wu; et al. (Global Change Biology, 2026)
Grasslands are widely recognized as important sinks of methane (CH 4 ). However, their CH 4 uptake capacity has been increasingly weakened driven by human activities and changes in precipitation regimes. In particular, the rapid expansion of livestock grazing can lead to substantial increases in CH 4 emissions. For the Eurasian grasslands that have been subject to long‐term grazing, how well they currently function and will continue to function as CH 4 sinks under the changing precipitation regimes remains uncertain. Here we conducted an 11‐year grazing‐gradient experiment to assess the combined effects of grazing intensity and precipitation variability on grassland CH 4 fluxes. We measured soil CH 4 uptake in a manipulative grazing experiment in both wet and dry years, estimated livestock‐derived CH 4 emissions, and examined a range of biotic and abiotic drivers, including vegetation attributes, soil properties, and microbial biomass, for short‐ (prior to the onset of the lagged response) and long‐term (the entire experimental period) influences on the dynamics of CH 4 uptake in temperate meadow grasslands. Over the long term, CH 4 fluxes are jointly regulated by precipitation and grazing, with overgrazing amplifying the suppressive effect of rainfall on CH 4 uptake. Soil CH 4 uptake showed a lagged response to grazing, which may have been triggered by extreme rainfall events. While moderate grazing sustained the long‐term CH 4 uptake, it fails to offset livestock‐derived CH 4 emissions. In the short term, CH 4 fluxes are primarily governed by grazing, whereas in the long term they are jointly regulated by precipitation and grazing intensity. These results offer a new perspective for understanding the source–sink CH 4 dynamics of grasslands in the context of ongoing climate change.

Coordination-tailored conductive metal-organic frameworks boost CO2 electroreduction to ethylene for cascade ethylene glycol production - Hui Guo; Shao-Shuai Zhao; Duan-Hui Si; Weijin Li; Zi-Ao Chen; Rong Cao; Roland A. Fischer; Yuan-Biao Huang (Science Bulletin, 2026)

Konjac glucomannan retards the deterioration of whey protein isolate gel quality after freeze-thaw cycles and their application in frozen skimmed yogurt - Hui-Ling Li; Xu-Mei Wang; Zong-Cai Tu; Jun Liu; Yan-Hong Shao (Food Hydrocolloids, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Efficient and selective capture of sulfur dioxide by graphitic phase carbon nitride equipped with BmimCl-type deep eutectic solvents - Yong-Hui Liu; Shao-He Wang; Jia-Yi Yi; Jin-bo Xu; Li-Ming Cheng; Jun Du (Environmental Research, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Topological and source–sink integrated analysis of urban thermal environment networks in a megacity: Longitudinal insights from Guangzhou - Liang Tang; Runyu Shao; Xinran Zhou; Yali Zhang; Ziyi Chen; Long Yang; Hui Li (Sustainable Cities and Society, 2026)

A novel Fucose-specific lectin from Morchella esculenta modulates gut-liver Axis to alleviate non-alcoholic fatty liver disease - Peng Liu; Chen Gao; Shengwei Li; Di Wu; Zhong Zhang; Wanchao Chen; Wen Li; Feng Shao; Hui-Min David Wang; Yan Yang (Food Research International, 2026)

Moderate grazing strengthens the responses of plant diversity and ANPP to climatic factors in semi-arid grasslands - Jing Hou; Jun Liu; Zhiyu Liu; Yunmeng Tang; Chen Liu; Xuekai Sun; Kaimeng Wang; Huimei Zhang; Siyu Li; Ling Wang; Deli Wang; De-Hui Zeng; et al. (Agriculture, Ecosystems & Environment, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

From metamorphic to magmatic fluids: Decoding of Yanshanian Au mineralization process in the Wangu gold deposit, southern China - Yong-shun Li; Yong-jun Shao; Zhong-fa Liu; Ke Chen; Xue-ling Dai; Ming-hui Chen; Ming-peng He; Qing Gou (Journal of Asian Earth Sciences, 2026)

A novel physics-guided collaborative modeling method for steady-state simulation of air source heat pump system - Lianyu Shan; Qingzhuang Wu; Mei Wang; Hui Zhang; Wenbo Li; Yanhua Guo; Shuangquan Shao; Zhuang Chen; Yaran Liang (International Journal of Refrigeration, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Changes in plant community composition and soil resource drive jointly fine root productivity response to grazing in a meadow steppe - Hui Li; Changliang Shao; Yuguang Ke; Xiaoping Xin; Ziwei Tao; Yufan Si; Haonan Guo; Cuixia Jiang; Ruirui Yan; Guozhen Du; Zihao Li; Feng Liu (Plant and Soil, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Tetrahydrocurcumin for Major Depressive Disorder with Therapeutic Potential and Mechanistic Insights from Clinical and Preclinical Studies - Ying Guo; Jianping Xie; Haiyun Luo; Yun Yuan; Fang Long; Jingyuan Meng; Hui Tan; Yuanping Li; Bibo Cai; Meiling Chen; Liyan Yang; Jingmei Zhong; et al. (Molecular Neurobiology, 2026)

Tree trunk disease mapping using hyperspectral LiDAR - Peilun Hu; Yuwei Chen; Wei Li; Huaguo Huang; Samuli Junttila; Shuanghui He; Yanan Zhao; Xiaoqi Cui; Mohammad Imangholiloo; Changhui Jiang; Jianxin Jia; Haibin Sun; et al. (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region” [Sci. Total Environ. 946 (2024) 174054] - Xiaoping Xin; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; Ruirui Yan; et al. (Science of The Total Environment, 2025)

A review of flexible fluid-structure interactions in the ocean: Progress, challenges, and future directions - Sasan Tavakoli; Mansi Singh; Saeed Hosseinzadeh; Zhengyu Hu; Yaniln Shao; Shan Wang; Luofeng Huang; Apostolos Grammatikopoulos; Yuzhu Pearl Li; Danial Khojasteh; Jin Liu; Azam Dolatshah; et al. (Ocean Engineering, 2025)

Molecular transformation of dissolved organic matter for shale gas flowback wastewater during ozonation treatment - Yun Kong; Qingyun Zhou; Jiamiao Li; Ziwei Zhou; Bin Wang; Wei Li; Yike Zhou; Yunjun Mei; Wenbin Hu; Hui Xu; Jin Shao; Qi Chen (Journal of Water Process Engineering, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Genetic loci and functional genes conferring deep-sowing tolerance across multiple environments in soybean - Rui Tian; Zhenqi Shao; Hua Zhang; Xinzhu Xing; Jiahao Chu; Youbin Kong; Zhanwu Yang; Wenlong Li; Hui Du; Huifeng Ke; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2025)

Dynamic model for charging tight gas reservoirs: A case study from the Xujiahe Formation in the Sichuan Basin, China - Haoming Shao; Min Wang; Junfeng Cui; Hui Jin; Dianshi Xiao; Yidong Jia; Wei Li; Xiaodie Guan; Chen Zhao; Tao Zhang (Marine and Petroleum Geology, 2025)

Environmental adaptive nanoplatform for bacteriotherapy - Wei Sun; Yang Bai; Xuefei Shao; Bowen Li; Haohua Yuan; Xuheng Chen; Run Yang; Yuan Liu; Shixiang Cheng; Yanguo Xi; Qing-hui Meng; Bin Zheng; et al. (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Warming coupled with uranium exposure can alter the marine microbial community and induce toxin accumulation in shellfish - Ran-li Wang; Qian Fu; Ge Yao; Jin-long Lai; Shao-heng Bao; Xue-gang Luo; Hui Jiang; Yu Zhang; Peng-gang Han (Journal of Environmental Radioactivity, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Discovery and Significance of Paleozoic Granite Porphyry in the Haidewula Uranium Deposit, East Kunlun Orogenic Belt, Northwest China - Jian-Hua Duan; Tong Liu; Jia-Wen Dai; Hui-Min Su; Yan-Qiang Li; Shao-Yong Jiang (Journal of Earth Science, 2025)

Chemical evaluation of aerosol particles in an intense Asian dust storm in a coastal city: Direct vs. reverse transport stages - Wenhua Wang; Hui Zhou; Ruihe Lyu; Wenmiao Li; Zhe Zhao; Xiuyan Zhou; Longyi Shao (Journal of Environmental Sciences, 2025)

Groundwater-mediated U–Th–Pb differential migration in monazites during hydrochemical weathering - Hao-Xiang Zhang; Shao-Yong Jiang; Wen-Tian Li; Wei Zhang; Hui-Min Su (Chemical Geology, 2025)

Discovery of indole-carbohydrazide hybrids as novel broad-spectrum fungicidal lead compound though membrane-targeting mechanism - Ying Wu; Li-Hui Shao; Xian-Qun Hu; Yu Long; Yuan-Yuan Wu; Pei-Bu Yu; Ai-Ping Yan; Long-Fei Li; Xiang Zhou; Song Yang (Molecular Diversity, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Impact of seasonal precipitation regimes on soil nitrogen transformation in a subtropical forest: Insights from a manipulation experiment - Yongkang Ji; Nan Ma; Petr Heděnec; Yan Peng; Kai Yue; Jianxiao Zhu; Hui Zhang; Junjiong Shao; Lita Yi; Cuihuan Li; Qiqian Wu; Yan Li (Plant and Soil, 2025)

Utilizing Octanoic Acid to Quantitatively Assess the Oxidation Status of PS80 - Yue Guo; Sisi Zhang; Jamie Ash; Stacey Helming; Rachel Mullen; Xuening Hu; Qingyan Hu; Jing Wang; Tse-Hong Chen; Shao-Chun Wang; Douglas Kamen; Biao Shen; et al. (Pharmaceutical Research, 2025)

Two new species of Russula sect. Heterophyllae (Russulaceae, Russulales) from Jiangxi Province, Eastern China - Lin-Ping Zhang; Li-Hui-Dong Zhao; Xin-Gui Le; Zhen-Wei Mao; Shao-Hua Huang (Mycological Progress, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

Inhibition potential against butyrylcholinesterase of stilbenes, bibenzyls, and dihydrophenanthrenes from Pholidota chinensis - Xiaoyue Dong; Shiwei Sun; Zhongbai Shao; Hui Wang; Kangping Sun; Xinyi Li; Yibo Wu; Wei Wang (Medicinal Chemistry Research, 2025)

GmEXPA11 facilitates nodule enlargement and nitrogen fixation via interaction with GmNOD20 under regulation of GmPTF1 in soybean - Xinzhu Xing; Hui Du; Zhanwu Yang; Hua Zhang; Na Li; Zhenqi Shao; Wenlong Li; Youbin Kong; Xihuan Li; Caiying Zhang (Plant Science, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Fluoride enrichment in geothermal waters based on H, O, Sr, and Li isotopes of the Taiyuan Basin, North China - Chang Lu; Ying Li; Xiaocheng Zhou; Yuwen Wang; Weiye Shao; Zhaojun Zeng; Zhaofei Liu; Dawei Liao; Hui Zhang; Huimin Mu (Journal of Asian Earth Sciences, 2025)

Laboratory investigation of sandstone joints and strata on TBM performance using a tunnelling test platform - Wei-Qiang Xie; Xiao-Li Liu; Shao-Hui Tang; Qi Zhang; Da-Rui Ren; Qing Ma (Engineering Geology, 2025)

Experimental study of thermal comfort by variable temperature and velocity air supply system in operating room - Bin Zhou; Ang Wang; Hui Ren; Jie Xia; Fan Peng; Shao-Cong Wang; Yi-Chu Wang; Hao-Yi Zhao; Wen-Jie Li; Mei-Lan Tan; Risto Kosonen (Building and Environment, 2025)

Enterococcus faecalis Exerts Neuroprotective Effects via the Vagus Nerve in a Mouse Model of Parkinson’s Disease - Xian Shao; Tao Wu; Mengyun Li; Matao Zheng; Hui Lin; Xuchen Qi (Molecular Neurobiology, 2025)

Proposal of Paenibacillus kandeliae sp. nov, Isolataed from Leaf of Kandelia candel - Cheng-Shao Zan; Xiao Ma; Xiao-Hui Chen; Ming-Sheng Chen; Li Tuo (Current Microbiology, 2025)

In situ global mapping of protein perturbations via protein abundance and conformation analysis - Yi Li; Xingchao Yang; Fei Zheng; Hanqing Zhang; Chang Shao; Ning Wan; Haiping Hao; Hui Ye (Analytica Chimica Acta, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Adhesion-Related Pathways and Functional Polarization of Astrocytes in Traumatic Brain Injury: Insights from Single-cell RNA Sequencing - Xiaoyan Liu; Ji Xia; Wenjing Shao; Xiaoming Li; Danfeng Yuan; Jingru Xie; Liang Zhang; Yuqian Tang; Hui Zhao; Pengfei Wu (NeuroMolecular Medicine, 2025)

Dynamic effects of Aeromonas sobria infection on intestinal morphology, microbiota and goblet cells of rainbow trout (Oncorhynchus mykiss) - Li-Ping Liu; Peng-Tian Kang; Feng-Yuan Ding; Dong-Hong Shao; Bao-Shan Wang; Juan Yang; Wen-Hui Gao; Wang-Dong Zhang; Wen-Hui Wang; Ji-Xing Liu (Aquaculture, 2025)

Improved ovalbumin accurate quantitative performance in processed foods by full-length isotope-labeled protein - Yige Wu; Sai Fan; Jing Sun; Kai Yao; Yunjia Yang; Qian Jiang; Jing Zhang; Xuan Wu; Meng Zhang; Shiyu Du; Hui Li; Bing Shao (Food Chemistry, 2025)

Development of a high-resolution near-surface meteorological forcing dataset for the Third Pole region - Yaozhi Jiang; Wenjun Tang; Kun Yang; Jie He; Changkun Shao; Xu Zhou; Hui Lu; Yingying Chen; Xin Li; Jiancheng Shi (Science China Earth Sciences, 2025)

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Insight into the effect of electric fields on bioremediation of petroleum-contaminated soil: A micro-ecological response - Sa Wang; Hui Li; Yaqi Jiao; Li Li; Qin Zhou; Hao Sun; Zhigou Shao; Changxian Wang; Jiawei Jing; Zishu Gao (Journal of Environmental Management, 2025)

Short-term electrical load forecasting based on pattern label vector generation - Haozhe Zhu; Qingcheng Lin; Xuefeng Li; Hui Xiao; Ting Shao (Energy and Buildings, 2025)

Control engineering for the construction of UiO-66 effectively increases adsorption performance: The role of solvent factor - Xuanyu Shi; Zhiwei Geng; Mingming Peng; Qiuyang Zuo; Hui Shi; Liming Yang; Zifei Wang; Yuan Ding; Xuan Ding; Xin Li; Zhennan Jin; Wenxing Huang; et al. (Environmental Science and Pollution Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mercury evidence for volcanism driving environmental changes during the protracted Late Ordovician mass extinction and early Silurian recovery - Yanfang Li; Hui Tian; Tongwei Zhang; Baojian Shen; Deyong Shao (Chemical Geology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Reproductive toxicity of bisphenol A and nitro-bisphenol A in male zebrafish at environmentally relevant concentrations - Chao Wang; Shuyi Zhang; Zijin Shao; Peijie Sun; Jiran Zhang; Shaoping Zhang; Jian Kong; Hong Zhi; Li Li; Mingshu Li; Jie Yu; Zhenming Liu; et al. (Science of The Total Environment, 2025)

Co-existence of a novel RND efflux pump tmexC6D6.2-toprJ1b and blaOXA-4 in the extensively drug-resistant Pseudomonas aeruginosa ST233 clone - Xuan Wu; Guorong Chen; Panpan Wang; Lu Yang; Yige Wu; Guoquan Wu; Hui Li; Bing Shao (International Journal of Food Microbiology, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Prediction and pathway models for assessing soil properties influencing soil selenium enrichment and bioavailability in Aksu Prefecture, northwest China - Hui Zhai; Yunshu Zhang; Wanli Xu; Wenyu Hou; Guangmu Tang; Chunhui Ge; Huawei Shao; Haotian Gong; Yujian Wang; Yumeng Liu; Lei Pan; Li Ling (Science of The Total Environment, 2024)

The CpCOR1 gene enhances cold tolerance and antioxidant activity of papaya fruit in response to postharvest chilling stress - Yuwei Nian; Muhammad Muzammal Aslam; Xin Wang; Hui Gu; Wen Li; Yuanzhi Shao (Postharvest Biology and Technology, 2024)

Morphology and elemental composition of individual solid dust particles: From different sources to the atmosphere - Wenhua Wang; Mengyang Wang; Longyi Shao; Xiuyan Zhou; Zhe Zhao; Na Li; Hui Zhou; Weijun Li (Atmospheric Environment, 2024)

Bioinformatics Analysis and Experimental Validation of Differential Genes and Pathways in Bone Nonunions - Wei Xiong; Xing-Li Shu; Lv Huang; Su-Qi He; Lang-Hui Liu; Song Li; Zi-Chen Shao; Jun Wang; Ling Cheng (Biochemical Genetics, 2024)

The effect of Desulfovibrio caledoniensis and Pseudomonas aeruginosa on the corrosion behaviour of 70Cu-30Ni alloy - Li-Jun He; Zheng-Hui Qiu; Shao-Xia Ma; Rong-Chang Zeng; Cun-Guo Lin (Biofouling, 2024)

Direct recovery of high-purity lithium via nanofiltration membranes from leaching solution of spent lithium batteries - Shiweihua He; Qiuyang Zuo; Hui Shi; Zhiwei Geng; Congcong Liu; Lin Ding; Xin Li; Penghui Shao; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2024)

Study of Cerchar abrasive parameters of monomineralic rocks and its application for evaluating cutting efficiency - Xin-Fang Li; Xiao-Ping Zhang; Shao-Hui Tang; Wei-Qiang Xie; Xin-Mei Yang; Quan-Sheng Liu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Design of a tubular segmented-in-series solid oxide fuel cell (SOFC): One-dimensional steady state modeling - Hui-Yu Zhang; Yun Liu; Shao-Dong Sun; Chang-Jiu Li; Cheng-Xin Li (Chemical Engineering Journal, 2024)

Microbial groups containing alkaline phosphatase accelerate soil phosphate mineralization in two soil patterns with contrasting pH levels - Hui Li; Jitong Lin; Qi Shao; Beibei Zhang; Yunting Wang; Linke Wang; Haojie Feng; Yanhong Lou; Hui Wang; Quangang Yang; Zhongchen Yang; Hongjie Di; et al. (Journal of Soils and Sediments, 2024)

Phage LysSA163-CBD mediated specific recognition coupled with ATP bioluminescence for the sensitive detection of viable Staphylococcus aureus in food matrices - Peng Guan; Ruining Li; Yifeng Ding; Chenxi Huang; Jia Wang; Hui Pan; Yanchun Shao; Xiaohong Wang (Analytica Chimica Acta, 2024)

Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region - Xiaoping Xin; Xueqi Lan; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; et al. (Science of The Total Environment, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

Utilizing Anionic-Pillared Metal-Organic frameworks for low carbon and efficient palladium recovery via constructing a waste-free cycle - Qingying Xiao; Hao Dong; Penghui Shao; Lingrong Zeng; Ziwen Chang; Guanyuan Gao; Ziwei Yao; Shuigen Li; Liming Yang; Hui Shi; Xubiao Luo; Shenglian Luo (Chemical Engineering Journal, 2024)

Capsaicin reduces blood glucose and prevents prostate growth by regulating androgen, RAGE/IGF-1/Akt, TGF-β/Smad signalling pathway and reversing epithelial-mesenchymal transition in streptozotocin-induced diabetic mice - Hui Sun; ZiTong Wang; BingHua Tu; ZiChen Shao; YiDan Li; Di Han; YinJie Jiang; Peng Zhang; WeiChang Zhang; YunYan Wu; XiaoMing Wu; Chi-Ming Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Association analysis of antibiotic and disinfectant resistome in human and foodborne E. coli in Beijing, China - Lu Yang; Xuan Wu; Guoquan Wu; Yige Wu; Hui Li; Bing Shao (Science of The Total Environment, 2024)

Enhanced acidic hydrogen evolution reaction kinetics via nitrogen-doped iridium nanosheet with optimized hydrogen adsorption energy - Qianyu Lin; Yixian Liu; Jiacheng Li; Kun Feng; Jun Zhong; Hui Huang; Mingwang Shao; Zhenglong Fan; Fan Liao; Yang Liu; Zhenhui Kang (Chemical Engineering Journal, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Cevanine-type steroidal alkaloids from the bulbs of Fritillaria cirrhosa D. Don - Hui-wen Dong; Shu-hui Wang; Tse Wai Ming; Shao-bing Fu; Yun-hu Zhang; Jia-wei Li; Qing-ying Zhang; Peng-fei Tu; Hong Liang (Phytochemistry, 2024)

Preparation of β-cyclodextrin-reduced graphene oxide aerogel and its application for adsorption of herbicides - Ting Yao; Hong Chen; Yue Luo; Hui Li; Xiaolan Shao; Qianqi Zheng; Dingdi Tu; Bei Yan; Jinfeng Dai; Lianyang Bai; Kailin Liu (Journal of Cleaner Production, 2024)

Aloe vera and tea polyphenols composite coating delays passion fruit senescence by promoting phenolic and flavonoid accumulation - Yu Wang; Muhammad Muzammal Aslam; Xin Wang; Hui Gu; Wenjun jia; Wen Li; Yuanzhi Shao (Food Research International, 2024)

New Discovery of the Jinshui Tin Deposit in the Middle Section of the East Kunlun Orogenic Belt, Northwestern China: Mineralization Age and Exploration Significance - Xingkai Zhang; Shao-Yong Jiang; Hui-Min Su; Wei Wang; Qinglin Xia; Yunpeng Liu; Shien Li (Journal of Earth Science, 2024)

Suppressing the virulence factors of Candida auris with baicalein through multifaceted mechanisms - Can Li; Jun Wang; Hao Li; Yemei Wang; Hui Wu; Wenfan Wei; Daqiang Wu; Jing Shao; Tianming Wang; Changzhong Wang (Archives of Microbiology, 2024)

Decoupling of gray and white matter functional networks in cognitive impairment induced by occupational aluminum exposure - Feifei Zhang; lina Li; Bo Liu; Yingbo Shao; Yan Tan; Qiao Niu; Hui Zhang (NeuroToxicology, 2024)

Prenatal exposure to fenvalerate causes depressive-like behavior in adulthood by inhibiting brain-derived 5-HT synthesis - Hui-Min Zhu; Bo Wang; Tao Wang; Jing Shao; Hui-Ru Chen; Chi Zhang; Li-Hua Xu; Jing-Jing Li; Min Wang; De-Xiang Xu; Xiu-Hong Meng (Environmental Pollution, 2024)

Nitrogen isotopes of released gas from rock crushing and implications to origins of molecular nitrogen in Lower Cambrian overmature shale gas in South China - Kang Meng; Tongwei Zhang; Deyong Shao; Zhongping Li; Liwu Li; Yu Zhang; Yan Liu; Hui Song (Marine and Petroleum Geology, 2024)

A SILAC-based accurate quantification of shrimp allergen tropomyosin in complex food matrices using UPLC-MS/MS - Yige Wu; Kai Yao; Yunjia Yang; Xuan Wu; Jing Zhang; Yushen Jin; Yang Xing; Yumin Niu; Qian Jiang; Chongshan Dai; Yang Wang; Hui Li; et al. (Food Chemistry, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Experimental study on the influence mechanism of soil additives on scraper wear during EPB-TBM tunnelling in abrasive sandy ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Wei-Qiang Xie; Jian Wu; Hao-Jie Wang; Xin-Fang Li (Bulletin of Engineering Geology and the Environment, 2024)

Progress of 3-ketosteroid Δ1-dehydrogenases for steroid production - Bo Zhang; Deng-Feng Zhou; Meng-Juan Li; Jia-Hui Lan; Hui Li; Ming-Long Shao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

Positive effects of vegetation restoration on the soil properties of post-mining land - Cuihuan Li; Yongkang Ji; Nan Ma; Jing Zhang; Hui Zhang; Chengjun Ji; Jiangling Zhu; Junjiong Shao; Yan Li (Plant and Soil, 2024)

Feasibility study of forest wood-boring pest detection base on hyperspectral LiDAR - Hui Shao; Hulong Zhang; Peilun Hu; Yuwei Chen; Wei Li; Long Sun; Yuxia Hu (International Journal of Remote Sensing, 2024)

Metal element-based adsorbents for phosphorus capture: Chaperone effect, performance and mechanism - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Chemosphere, 2024)

Efficient recycling of Au(S2O3)23− from alkaline leach solutions using diphenylamine-rich Cu-MOF via local exotherms of DMF - Qingying Xiao; Hao Dong; Bo Li; Jianzhi Zhang; Lili Fang; Ziwei Yao; Lingrong Zeng; Liming Yang; Hui Shi; Xubiao Luo; Penghui Shao (Resources, Conservation and Recycling, 2024)

pH-Responsive Janus membrane with liquid gating property for crop protection and demulsification - Liming Liu; Jiahao Luan; Shishun Li; Chen Shao; Tianyun Dong; Yong Chen; Hui You (Chemical Engineering Journal, 2024)

Effects of flue gas desulfurization gypsum and clover planting on qualities of soil and winter jujube in coastal saline-alkali orchard of north China - Qi Shao; Xuejing Xia; Guihua Li; Hui Li; Jitong Lin; Yanhong Lou; Quangang Yang; Hui Wang; Zhongchen Yang; Hong Pan; Yuping Zhuge (Soil Ecology Letters, 2024)

Pyrolysis temperature matters: Biochar-derived dissolved organic matter modulates aging behavior and biotoxicity of microplastics - Honghong Lyu; Hui Zhang; Jinrui Dong; Boxiong Shen; Zi Cheng; Junhui Yu; Ruiyan Li; Ningning Shao; Jingchun Tang (Water Research, 2024)

Metatranscriptomic insights into the microbial metabolic activities during an Ulva prolifera green tide in coastal Qingdao areas - Xinyi Wang; Hao Yu; Yan Li; Qianru Fu; Hongbing Shao; Hui He; Min Wang (Environmental Pollution, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

Chemical composition and morphology of PM2.5 in a rural valley during Chinese New Year's Eve: Impact of firework/firecracker display - Wenhua Wang; Hui Zhou; Yutao Gao; Longyi Shao; Xiuyan Zhou; Xian Li; Dongqing Wei; Jiaoping Xing; Ruihe Lyu (Atmospheric Environment, 2024)

Two new lactam derivatives from a Sphagneticola trilobata derived fungus Penicillium rubens PQJ-2 - Wen-xing Li; Xiu-qiao Zhou; Shao-dong Ji; Yi-nuo Wang; Zhen-fan Sun; Zi-yi Huang; Zi-ming Zhou; Yang Hui; Wen-hao Chen (Natural Product Research, 2024)

Aerobic Glycolysis Induced by mTOR/HIF-1α Promotes Early Brain Injury After Subarachnoid Hemorrhage via Activating M1 Microglia - Xin-Gang Sun; Xue-Hong Chu; Ivan Steve Godje Godje; Shao-Yu Liu; Hui-Yu Hu; Yi-Bo Zhang; Li-Juan Zhu; Hai Wang; Chen Sui; Juan Huang; Ying-Jie Shen (Translational Stroke Research, 2024)

Corrigendum to “Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus” [Aquaculture 578(15): 740130, 2024] - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Algal growth and alkaline phosphatase activity of ‘green tide’ Chaetomorpha linum in response to phosphorus stress - Jia-Hui Xie; Xue-Lin Shao; Kai Ma; Li Gao (Journal of Marine Systems, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Mechanically stable superhydrophobic coating of crosslinked polymer composite with self-healing ability - Xiao-Jing Guo; Meng-Chen Huang; Chao-Hua Xue; Hui-Di Wang; Zhong-Xue Bai; Yong-Gang Wu; Chao-Qun Ma; Zhong-Yang Shao; Zi-Hao Jiang; Li Wan; A-Jun Chang; Jing Li; et al. (Chemical Engineering Journal, 2024)

Modifying the active phase structure of Ni2P/Al2O3 by Ga introduction for improved hydrodesulfurization of diesel - Shuhui Zhou; Zejian Wu; Jixing Liu; Yan Wang; Shijia Shao; Feng Liu; Huifang Cheng; Hui Liu; Huaming Li; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Rationally designed calcium carbonate multifunctional trap for contaminants adsorption - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Science of The Total Environment, 2023)

Structurally diverse terpenoids from Elephantopus scaber L. and their acetylcholinesterase inhibitory activities - Jia-Yi Li; Shu-Hui Dong; Xin Zhang; Zi-Jian Liu; Jin-Le Hao; Bin Lin; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Selective capture of palladium from acid wastewater by thiazole-modified activated carbon: Performance and mechanism - Li Zhang; Bo Li; Penghui Shao; Xiaoyu Zhou; Dewei Li; Zichao Hu; Hao Dong; Liming Yang; Hui Shi; Xubiao Luo (Environmental Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The alkaloids with neuroprotective effect from the root bark of Ailanthus altissima - Qing Shao; Tian-Yi Li; Wei Quan; Hui Wang; Ke-Yu Yan; Peng-Cheng Qiu; Hai-Feng Tang; Yun-Yang Lu (Natural Product Research, 2023)

Fast perception of rock mass strength and integrity in TBM tunnelling using in-situ penetration test - Wei-Qiang Xie; Xiao-Ping Zhang; Shao-Hui Tang; Xiao-Li Liu; Xin-Fang Li; Qi Zhang; Fa-Yuan Yan; Chen Xu; Quan-Sheng Liu (Tunnelling and Underground Space Technology, 2023)

Enhancing data reliability in quantitative characterization of moisture distribution in sludge using DSC: Impact of sample attributes and test parameters - Ya-Li Zhang; Hao Zhang; Wen-Hui Liu; Ping Sun; Shao-Ming Zheng; Yun-Yan Gao; Yuan-Ping Zeng; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Environmental Management, 2023)

LNAPL migration processes based on time-lapse electrical resistivity tomography - Zhi-ping Li; Yu Liu; Gui-zhang Zhao; Shao-kang Liu; Wen-hui Liu (Journal of Contaminant Hydrology, 2023)

The metabolism of membrane lipid participates in the occurrence of chilling injury in cold-stored banana fruit - Qian Li; Han Lin; He-tong Lin; Meng-shi Lin; Hui Wang; Wei Wei; Jian-ye Chen; Wang-jin Lu; Xing-feng Shao; Zhong-qi Fan (Food Research International, 2023)

Zebrafish nos2a benefits bacterial proliferation via suppressing ROS and inducing NO production to impair the expressions of inflammatory cytokines and antibacterial genes - Si Yao Zheng; Xinbin Shao; Zhitao Qi; Maocang Yan; Min Hui Tao; Xiao Man Wu; Lining Zhang; Jianzhong Ma; An Li; Ming Xian Chang (Fish & Shellfish Immunology, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

Associating phthalate exposure during pregnancy with preschooler's FMI, ABSI and BRI trajectories via putative mechanism pathways - Hui Gao; Yi Zhang; Li-wen Chen; Hong Gan; Meng-juan Lu; Binbin Huang; Juan Tong; Meng-long Geng; Kun Huang; Cheng Zhang; Bei-bei Zhu; Shan-shan Shao; et al. (Chemosphere, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Spread of multidrug-resistant Pseudomonas aeruginosa in animal-derived foods in Beijing, China - Xuan Wu; Lu Yang; Yige Wu; Hui Li; Bing Shao (International Journal of Food Microbiology, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Wuzi Yanzong Pill relieves MPTP-induced motor dysfunction and neuron loss by inhibiting NLRP3 inflammasome-mediated neuroinflammation - Tao Pan; Qi Xiao; Hui-Jie Fan; Lei Xu; Shao-Chen Qin; Li-Xia Yang; Xiao-ming Jin; Bao-Guo Xiao; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Pyrite coupled with steel slag to enhance simultaneous nitrogen and phosphorus removal in constructed wetlands - Ying Liu; Xiao-Hui Liu; Hong-Cheng Wang; Zhi-Ling Li; Bin Liang; Yi-Lu Sun; Hao-Yi Cheng; Shao-Yong Lu; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Mechanistic investigation of the differential synergistic neurotoxicity between pesticide metam sodium and copper or zinc - Chen Shen; Zhi-Guo Sheng; Jie Shao; Miao Tang; Li Mao; Chun-Hua Huang; Zhi-Hui Zhang; Ben-Zhan Zhu (Chemosphere, 2023)

Decomplexation of Ni-EDTA by thermally activated persulfate: Efficiency and mechanism - Xinkai Yuan; Wei Xiong; Yanhua Peng; Bo Li; Jianzhi Zhang; Meiling Chen; Xiuqin Xiong; Liming Yang; Hui Shi; Xubiao Luo; Penghui Shao (Journal of Water Process Engineering, 2023)

Integrated effect of bulk cations on nano-confined reactivity of clay-intercalated subnanoscale zero-valent iron in water-tetrahydrofuran mixtures - Kai Yu; Yanni Lv; Haowen Jiang; Huimin Li; Penghui Shao; Liming Yang; Hui Shi; Zhong Ren; Cun Liu; Xubiao Luo (Journal of Hazardous Materials, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

Resveratrol and Sir2 Reverse Sleep and Memory Defects Induced by Amyloid Precursor Protein - Yuping Hao; Lingzhan Shao; Jianan Hou; Yan Zhang; Yuqian Ma; Jinhao Liu; Chuan Xu; Fujun Chen; Li-Hui Cao; Yong Ping (Neuroscience Bulletin, 2023)

Rapid extraction of valuable metals from spent LiNixCoyMn1-x-yO2 cathodes based on synergistic effects between organic acids - Jianzhi Zhang; Xingyu Hu; Tingting He; Xinkai Yuan; Xin Li; Hui Shi; Liming Yang; Penghui Shao; Chaoqiang Wang; Xubiao Luo (Waste Management, 2023)

One-pot synthesis of ZnIn2S4 graphene aerogels with S vacancies for efficient photocatalytic reduction of Cr(VI) and hydrogen evolution - Haiyang Liu; Feng Sun; Hong Shao; Duanduan Yin; Xinyue Li; Qianli Ma; Guixia Liu; Hui Yu; Wensheng Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2023)

Selective capture of palladium by protonation-armed pyridine nitrogen in extreme water environments - Dewei Li; Lei Zhou; Min Li; Jifeng Yang; Ziwei Yao; Li Zhang; Zhu Meng; Liming Yang; Hui Shi; Huan Tang; Xubiao Luo; Shenglian Luo; et al. (Chemical Engineering Journal, 2023)

Occurrence, risk, and treatment of ciprofloxacin and clarithromycin in drainage - Meng Li; Dengyu Ji; Malvin Subroto Pamudji; Ka Hei Lui; Yayi Zhao; Gaoshen Zhao; Shao-Qi Zhou; Ce-Hui Mo; Wei Han; King Lun Yeung (Chemical Engineering Journal, 2023)

Schisandrin B Improves the Hypothermic Preservation of Celsior Solution in Human Umbilical Cord Mesenchymal Stem Cells - Ying Zhang; Peng Wang; Mei-xian Jin; Ying-qi Zhou; Liang Ye; Xiao-juan Zhu; Hui-fang Li; Ming Zhou; Yang Li; Shao Li; Kang-yan Liang; Yi Wang; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Genome resequencing reveals genetic loci and genes conferring resistance to SMV-SC8 in soybean - Jiahao Chu; Wenlong Li; Zhanwu Yang; Zhenqi Shao; Hua Zhang; Shaoda Rong; Youbin Kong; Hui Du; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Shewanella subflava sp. nov., a novel multi-resistant bacterium, isolated from the estuary of the Fenhe River into the Yellow River - Bi Luo; Jing-Yun Su; Ya-Nan Wang; Li Guan; Kai-Shi Dong; Hui-Jing Niu; Shao-Fei Shen; Yi Li (Antonie van Leeuwenhoek, 2023)

Calcium-modified biochar rather than original biochar decreases salinization indexes of saline-alkaline soil - Hui Li; Baojie Wang; Muji Siri; Cheng Liu; Changliang Feng; Xinqing Shao; Kesi Liu (Environmental Science and Pollution Research, 2023)

Comprehensive metabolomic profiling of nutrients in fish and shrimp - Chang Shao; Yang Su; Duanyue Meng; Yi Li; Yuanyuan Dong; Haiping Hao; Hui Ye (Food Chemistry, 2023)

Prediction of the instability probability for rainfall induced landslides: the effect of morphological differences in geomorphology within mapping units - Kai Wang; Shao-jie Zhang; Wan-li Xie; Hui Guan (Journal of Mountain Science, 2023)

Bioaccessibility and bioavailability of NPAHs in soils using in vitro-in vivo assays: Comparison of laboratory and outdoor environmental aging effect - Xian-Xian Chen; Chao Li; Xiao-Yu Cao; Krishna Kumar Selvaraj; Hui-Ming Li; Feng-Xiao Zhu; Shao-Gui Yang; Shi-Yin Li; Li-Min Zhang; Huan He (Science of The Total Environment, 2023)

Genetic structure, major chemical component contents and agronomic characters of the principal cultivars of the kelp Saccharina japonica in the largest kelp production province in China - Xiao Dong Li; Chen Hui Zhong; Zhen Hui Jin; Qi Lin; Ti Feng Shan; Shao Jun Pang (Journal of Applied Phycology, 2023)

Sodium acetate alleviates adverse effects caused by the diet with high proportion of soybean meal in turbot (Scophthalmus maximus L.) - Wentao Wang; Jinjin Zhang; Rui Shao; Shufei Liang; Hui Zhang; Weiqi Xu; Mingzhu Li; Qinghui Ai; Kangsen Mai; Min Wan (Aquaculture, 2023)

Porous phosphomolybdate-based poly(ionic liquid) hybrids with reversible water absorption for enhancement of oxidative desulfurization - Shao-Xu Mao; Qi-Hang Zhou; Hui-Li Guo; Ming Du; Wen-Shuai Zhu; Hua-Ming Li; Jing-Yu Pang; Dong-Bin Dang; Yan Bai (Fuel, 2023)

Rapid charge transfer in covalent organic framework via through-bond for enhanced photocatalytic CO2 reduction - Li-Juan Gong; Li-Yao Liu; Shao-Shuai Zhao; Shuai-Long Yang; Duan-Hui Si; Qiu-Jin Wu; Qiao Wu; Yuan-Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

Hearing of Otof-deficient mice restored by trans-splicing of N- and C-terminal otoferlin - Honghai Tang; Hui Wang; Shengyi Wang; Shao Wei Hu; Jun Lv; Mengzhao Xun; Kaiyu Gao; Fang Wang; Yuxin Chen; Daqi Wang; Wuqing Wang; Huawei Li; et al. (Human Genetics, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Anoxic iron electrocoagulation automatically modulates dissolved oxygen and pH for fast reductive decomplexation and precipitation of Cu(II)-EDTA: The critical role of dissolved Fe(II) - Shiwei Xie; Chang Li; Hui Zhan; Wei Shao; Yuanxin Zhao; Peng Liu; Peng Liao (Journal of Hazardous Materials, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

One-step fabrication of self-healing poly(thioctic acid) coatings on ZE21B Mg alloys for enhancing corrosion resistance, anti-bacterial/oxidation, hemocompatibility and promoting re-endothelialization - Zhao-Qi Zhang; Pei-Duo Tong; Li Wang; Zheng-Hui Qiu; Jing-An Li; Hang Li; Shao-Kang Guan; Cun-Guo Lin; Hong-Yan Wang (Chemical Engineering Journal, 2023)

Key technology for the construction and inspection of long-distance underwater tunnel for 1000 kV gas-insulated transmission line - Xiao-Ping Zhang; Shao-Hui Tang; Quan-Sheng Liu; Hao-Jie Wang; Xin-Fang Li; Peng Chen; Hao Liu (Bulletin of Engineering Geology and the Environment, 2023)

N2O emissions from soils under short-term straw return in a wheat-corn rotation system are associated with changes in the abundance of functional microbes - Jitong Lin; Zhiyu Xu; Yinghao Xue; Renhua Sun; Rongguang Yang; Xiaoxu Cao; Hui Li; Qi Shao; Yanhong Lou; Hui Wang; Quangang Yang; Hong Pan; et al. (Agriculture, Ecosystems & Environment, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Panel data analysis of energy conservation and emission reduction on high-quality development of logistics industry in Yangtze River Delta of China - Linbang Fan; Hui Liu; Zhaoxia Shao; Cunfang Li (Environmental Science and Pollution Research, 2022)

Contrasting effects of altered precipitation regimes on soil nitrogen cycling at the global scale - Qiqian Wu; Kai Yue; Yuandan Ma; Petr Heděnec; Yanjiang Cai; Jian Chen; Hui Zhang; Junjiong Shao; Scott X. Chang; Yan Li (Global Change Biology, 2022)
Changes in precipitation regimes can strongly affect soil nitrogen (N) cycling in terrestrial ecosystems. However, whether altered precipitation regimes may differentially affect soil N cycling between arid and humid biomes at the global scale is unclear. We conducted a meta‐analysis using 1036 pairwise observations collected from 194 publications to assess the effects of increased and decreased precipitation on the input (N return from plants), storage (various forms of N in soil), and output (gaseous N emissions) of soil N in arid versus humid biomes at the global scale. We found that (1) increased precipitation significantly increased N input (+12.1%) and output (+34.9%) but decreased N storage (−13.7%), while decreased precipitation significantly decreased N input (−10.7%) and output (−34.8%) but increased N storage (+11.1%); (2) the sensitivity of soil N cycling to increased precipitation was higher in arid regions than in humid regions, while that to decreased precipitation was lower in arid regions than in humid regions; (3) the effect of altered precipitation regimes on soil N cycling was independent of precipitation type (i.e., rainfall vs. snowfall); and (4) the mean annual precipitation regulated soil N cycling in precipitation alteration experiments at the global scale. Overall, our results clearly show that the response of soil N cycling to increased versus decreased precipitation differs between arid and humid regions, indicating the uneven effect of climate change on soil N cycling between these two contrasting climate regions. This implies that ecosystem models need to consider the differential responses of N cycling to altered precipitation regimes in different climatic conditions under future global change scenarios.

The effects of polyethersulfone and Nylon 6 micromembrane filters on the pyraclostrobin detection: adsorption performance and mechanism - Xiaolan Shao; Lejun Liu; Hui Li; Yue Luo; Jingyu Zhao; Shuai Liu; Bei Yan; Dan Wang; Kun Luo; Min Liu; Lianyang Bai; Xiaoyun Li; et al. (Environmental Science and Pollution Research, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Identification of closely associated SNPs and candidate genes with seed size and shape via deep re-sequencing GWAS in soybean - Zhenqi Shao; Jiabiao Shao; Xiaobo Huo; Wenlong Li; Youbin Kong; Hui Du; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2022)

Isolation and Complete Sequence of One Novel Marine Bacteriophage PHS21 Infecting Pseudoalteromonas marina - Yan Li; Huifang Li; Yong Jiang; Hongbing Shao; Hui He; Min Wang (Current Microbiology, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Genetic loci and responsible genes for pod and seed traits under diverse environments via linkage mapping analysis in soybean [Glycine max (L.) Merr.] - Shiliang Chen; Yaqian Sun; Zhenqi Shao; Jiahao Chu; Wenlong Li; Youbin Kong; Hui Du; Xihuan Li; Caiying Zhang (Genetic Resources and Crop Evolution, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Phylogeographic pattern of a cryptoviviparous mangrove, Aegiceras corniculatum, in the Indo-West Pacific, provides insights for conservation actions - Achyut Kumar Banerjee; Hui Feng; Yuting Lin; Zhuangwei Hou; Weixi Li; Huiyu Shao; Zida Luo; Wuxia Guo; Yelin Huang (Planta, 2022)

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Variations in soil properties rather than functional gene abundances dominate soil phosphorus dynamics under short-term nitrogen input - Bing Han; Jingjing Li; Kesi Liu; Hui Zhang; Xiaoting Wei; Xinqing Shao (Plant and Soil, 2021)

High-K calc-alkaline to shoshonitic intrusions in SE Tibet: implications for metasomatized lithospheric mantle beneath an active continental margin - Ren-Zhi Zhu; Ewa Słaby; Shao-Cong Lai; Li-Hui Chen; Jiangfeng Qin; Chao Zhang; Shaowei Zhao; Fangyi Zhang; Wen-hang Liu; Mike Fowler (Contributions to Mineralogy and Petrology, 2021)

Characterization, Sources and Excessive Cancer Risk of PM2.5-Bound Polycyclic Aromatic Hydrocarbons in Different Green Spaces in Lin’an, Hangzhou, China - Fang Huang; Yinke Zhang; Yilei Lou; Xiaolu Li; Tianran Zhang; Hui Yu; Chuyang Yuan; Qun Tong; Feng Qi; Feng Shao (Bulletin of Environmental Contamination and Toxicology, 2021)

An experimental study on cutting tool hardness optimization for shield TBMs during dense fine silty sand ground tunneling - Xiao-Ping Zhang; Shao-Hui Tang; Quan-Sheng Liu; Xin-Bin Tu; Peng Chen; Fang-Yi Li (Bulletin of Engineering Geology and the Environment, 2021)

Effects of prenatal exposure to bisphenols on newborn leucocyte telomere length: a prospective birth cohort study in China - Jun Liang; Yantao Shao; Dongping Huang; Chunxiu Yang; Tao Liu; Xiaoyun Zeng; Chunling Li; Zhenghua Tang; Jennifer Tan Hui Juan; Yanye Song; Shun Liu; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2021)

Efficient Editing of an Adenoviral Vector Genome with CRISPR/Cas9 - Qiang Li; Hui Wang; Chen-yu Gong; Zhao Chen; Jia-xing Yang; Hong-wei Shao; Wen-feng Zhang (Indian Journal of Microbiology, 2021)

Downregulation of miR-296-3p by highly pathogenic porcine reproductive and respiratory syndrome virus activates the IRF1/TNF-α signaling axis in porcine alveolar macrophages - Yanbing Zhang; Xiao Xiang; Yan Lu; Hui Li; Abdul Wahaab; Mona Sharma; Ke Liu; Jianchao Wei; Zongjie Li; Donghua Shao; Beibei Li; Zhiyong Ma; et al. (Archives of Virology, 2021)

A Fluorogenic and Chromogenic Probe Distinguishes Fluoride Anions and Thiols: Implications for Discrimination of Fluoride-Containing G Series and Sulfur-Containing V Series Nerve Agents - Wei-hui Wu; Xin Wang; Liang Zong; Dan Li; Yan-hua Xiao; Shao-hui Sui; Jian Li; Meng Liu; Gao-yun Chen; Teng Luo; Min Liu; Xin-ming Wang; et al. (Journal of Fluorescence, 2021)

Models and measurements of seven years of evapotranspiration on a high elevation site on the Central Tibetan Plateau - Li-hui Wang; Xiao-bo He; Jakob F. Steiner; Dong-wei Zhang; Jin-kui Wu; Shao-yong Wang; Yong-jian Ding (Journal of Mountain Science, 2020)

A practical method for employing multi-spectral LiDAR intensities in points cloud classification - Changhui Jiang; Yuwei Chen; Wenxin Tian; Haohao Wu; Wei Li; Hui Zhou; Hui Shao; Shaojing Song; Eetu Puttonen; Juha Hyyppä (International Journal of Remote Sensing, 2020)

A pair of new diastereoisomeric phenylpropanoid-substituted flavan from the leaves of Ilex centrochinensis - Hui Long; Yu Chen; Ze-Hua Hu; Shao-Jun Zhang; Lu-Jun Li (Natural Product Research, 2020)

Anxiolytic Effect of Increased NREM Sleep after Acute Social Defeat Stress in Mice - Xiang Feng; Hui-Ying Zhao; Yu-Jin Shao; Hui-Fang Lou; Li-Ya Zhu; Shumin Duan; Yan-Qin Yu (Neuroscience Bulletin, 2020)
Social defeat stress (SDS) plays a major role in the pathogenesis of psychiatric disorders like anxiety and depression. Sleep is generally considered to involve recovery of the brain from prior experience during wakefulness and is altered after acute SDS. However, the effect of acute SDS on sleep/wake behavior in mice varies between studies. In addition, whether sleep changes in response to stress contribute to anxiety is not well established. Here, we first investigated the effects of acute SDS on sleep/wake states in the active period in mice. Our results showed that total sleep time (time in rapid eye-movement [REM] and non-REM [NREM] sleep) increased in the active period after acute SDS. NREM sleep increased mainly during the first 3 h after SDS, while REM sleep increased at a later time. Then, we demonstrated that the increased NREM sleep had an anxiolytic benefit in acute SDS. Mice deprived of sleep for 1 h or 3 h after acute SDS remained in a highly anxious state, while in mice with ad libitum sleep the anxiety rapidly faded away. Altogether, our findings suggest an anxiolytic effect of NREM sleep, and indicate a potential therapeutic strategy for anxiety.

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Biallelic NF1 inactivation in high grade serous ovarian cancers from patients with neurofibromatosis type 1 - Eliza Courtney; Sock Hoai Chan; Shao Tzu Li; Diana Ishak; Khurshid Merchant; Tarryn Shaw; Wen Yee Chay; Felicia Hui Xian Chin; Wai Loong Wong; Adele Wong; Joanne Ngeow (Familial Cancer, 2020)

Miscanthus cultivation shapes rhizosphere microbial community structure and function as assessed by Illumina MiSeq sequencing combined with PICRUSt and FUNGUIld analyses - Yan Chen; Wei Tian; Yang Shao; Ying-Jun Li; Li-An Lin; Ying-Jun Zhang; Hui Han; Zhao-Jin Chen (Archives of Microbiology, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Biofertilizers with beneficial rhizobacteria improved plant growth and yield in chili (Capsicum annuum L.) - Jing-Yi Gou; Sheng-Zhou Suo; Kun-Zhong Shao; Qi Zhao; Dan Yao; Hui-Ping Li; Jin-Lin Zhang; Christopher Rensing (World Journal of Microbiology and Biotechnology, 2020)

Local residents’ perceptions of climate and ecological changes in the eastern Tibetan Plateau - Zhongda Hu; Yuandong Zhang; Fengxue Gu; Yaobin Li; Hui Shao; Shirong Liu (Regional Environmental Change, 2020)

Review of drought impacts on carbon cycling in grassland ecosystems - Tianjie Lei; Jie Feng; Cuiying Zheng; Shuguang Li; Yang Wang; Zhitao Wu; Jingxuan Lu; Guangyuan Kan; Changliang Shao; Jinsheng Jia; Hui Cheng (Frontiers of Earth Science, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Controlled Release of Spirotetramat Using Starch–Chitosan–Alginate-Encapsulation - Yan-Li Xie; Wayne Jiang; Fen Li; Yu Zhang; Xiao-Yu Liang; Meng Wang; Xueqing Zhou; Shao-Ying Wu; Cheng-Hui Zhang (Bulletin of Environmental Contamination and Toxicology, 2020)

Short hairpin RNAs targeting M and N genes reduce replication of porcine deltacoronavirus in ST cells - Wen-yuan Gu; Yan Li; Bao-jing Liu; Jing Wang; Guang-fu Yuan; Shao-jie Chen; Yu-Zhu Zuo; Jing-Hui Fan (Virus Genes, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Determination of Alternaria toxins in drinking water by ultra-performance liquid chromatography tandem mass spectrometry - Yaoting Zhang; Hui Li; Jing Zhang; Bing Shao (Environmental Science and Pollution Research, 2019)

Impaired Hypothalamic Regulation of Sympathetic Outflow in Primary Hypertension - Jing-Jing Zhou; Hui-Jie Ma; Jian-Ying Shao; Hui-Lin Pan; De-Pei Li (Neuroscience Bulletin, 2019)

Expression and function analysis of a rice OsHSP40 gene under salt stress - Xin Wang; Huan Zhang; Lu-Yuan Shao; Xin Yan; Hui Peng; Jie-Xiu Ouyang; Shao-Bo Li (Genes & Genomics, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

Reconstruction of Y-chromosome phylogeny reveals two neolithic expansions of Tibeto-Burman populations - Ling-Xiang Wang; Yan Lu; Chao Zhang; Lan-Hai Wei; Shi Yan; Yun-Zhi Huang; Chuan-Chao Wang; Swapan Mallick; Shao-Qing Wen; Li Jin; Shu-Hua Xu; Hui Li (Molecular Genetics and Genomics, 2018)

The relationship between putamen-SMA functional connectivity and sensorimotor abnormality in ESRD patients - Dun Ding; Peng Li; Xue-ying Ma; Wang-huan Dun; Shi-feng Yang; Shao-hui Ma; Hong-juan Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

QTL mapping of pre-harvest sprouting resistance in a white wheat cultivar Danby - Mingqin Shao; Guihua Bai; Trevor W. Rife; Jesse Poland; Meng Lin; Shubing Liu; Hui Chen; Tadele Kumssa; Allan Fritz; Harold Trick; Yan Li; Guorong Zhang (Theoretical and Applied Genetics, 2018)

The effect of temperature on the developmental rates of seedling emergence and leaf-unfolding in two dwarf bamboo species - Shuyan Lin; Lijuan Shao; Cang Hui; Hardev S. Sandhu; Tingting Fan; Li Zhang; Fang Li; Yulong Ding; Peijian Shi (Trees, 2018)

Life cycle assessment and optimization analysis of different LNG usage scenarios - Yun Zhang; Hui Jiang; Jinhua Li; Shuai Shao; Haochen Hou; Yu Qi; Shushen Zhang (The International Journal of Life Cycle Assessment, 2018)

Whole sequence analysis indicates a recent southern origin of Mongolian Y-chromosome C2c1a1a1-M407 - Yun-Zhi Huang; Lan-Hai Wei; Shi Yan; Shao-Qing Wen; Chuan-Chao Wang; Ya-Jun Yang; Ling-Xiang Wang; Yan Lu; Chao Zhang; Shu-Hua Xu; Da-Li Yao; Li Jin; et al. (Molecular Genetics and Genomics, 2018)

Phthalate exposure and high blood pressure in adults: a cross-sectional study in China - Shao-hui Zhang; Ya-xin Shen; Lin Li; Tong-tong Fan; Yan Wang; Ning Wei (Environmental Science and Pollution Research, 2018)

In Situ Observation of Rock Spalling in the Deep Tunnels of the China Jinping Underground Laboratory (2400 m Depth) - Xia-Ting Feng; Hong Xu; Shi-Li Qiu; Shao-Jun Li; Cheng-Xiang Yang; Hao-Sen Guo; Yuan Cheng; Yao-Hui Gao (Rock Mechanics and Rock Engineering, 2018)

Estimation of oxygen effective diffusion coefficient in a non-steady-state biofilm based on response time - Jian-Hui Wang; Hai-Yan Li; You-Peng Chen; Shao-Yang Liu; Peng Yan; Yu Shen; Jin-Song Guo; Fang Fang (Environmental Science and Pollution Research, 2018)

Dispersals of the Siberian Y-chromosome haplogroup Q in Eurasia - Yun-Zhi Huang; Horolma Pamjav; Pavel Flegontov; Vlastimil Stenzl; Shao-Qing Wen; Xin-Zhu Tong; Chuan-Chao Wang; Ling-Xiang Wang; Lan-Hai Wei; Jing-Yi Gao; Li Jin; Hui Li (Molecular Genetics and Genomics, 2018)

Optimisation of steam distillation extraction oil from onion by response surface methodology and its chemical composition - Zhao Dan Wang; Li Hua Li; Hui Xia; Feng Wang; Li Gang Yang; Shao Kang Wang; Gui Ju Sun (Natural Product Research, 2018)

Abnormal structure and functional connectivity of the anterior insula at pain-free periovulation is associated with perceived pain during menstruation - Wang-huan Dun; Jing Yang; Ling Yang; Dun Ding; Xue-ying Ma; Feng-Li Liang; Karen M. von Deneen; Shao-hui Ma; Xiao-ling Xu; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2017)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Establishment of a markerless gene deletion system in Chromohalobacter salexigens DSM 3043 - Ya-Hui Shao; Li-Zhong Guo; Hao Yu; Bai-Suo Zhao; Wei-Dong Lu (Extremophiles, 2017)

Overexpression of PLK3 Mediates the Degradation of Abnormal Prion Proteins Dependent on Chaperone-Mediated Autophagy - Hui Wang; Chan Tian; Jing Sun; Li-Na Chen; Yan Lv; Xiao-Dong Yang; Kang Xiao; Jing Wang; Cao Chen; Qi Shi; Qi-Xiang Shao; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Different Response Patterns of Soil Respiration to a Nitrogen Addition Gradient in Four Types of Land-Use on an Alluvial Island in China - Deping Zhai; Wanyu Jin; Junjiong Shao; Yanghui He; Guodong Zhang; Ming Li; Hui Huang; Xuhui Zhou (Ecosystems, 2017)

The Involvement of NR2B and tau Protein in MG132-Induced CREB Dephosphorylation - Min Xie; Yuan Li; Shao-hui Wang; Qun-tao Yu; Xin Meng; Xiao-mei Liao (Journal of Molecular Neuroscience, 2017)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

New milbemycin metabolites from the genetically engineered strain Streptomyces bingchenggensis BCJ60 - Jian-Song Li; Min-Na Du; Hui Zhang; Ji Zhang; Shao-Yong Zhang; Hai-Yan Wang; An-Liang Chen; Ji-Dong Wang; Wen-Sheng Xiang (Natural Product Research, 2017)

Nr3C1-Bhlhb2 Axis Dysregulation Is Involved in the Development of Attention Deficit Hyperactivity - Li Hui Wu; Wei Cheng; Mei Yu; Bao Mei He; Hui Sun; Qi Chen; Yi Wei Dong; Xiao Ting Shao; Qian Qian Cai; Min Peng; Xing Zhong Wu (Molecular Neurobiology, 2017)

Dating of the topmost terrace in the Jingxian Basin, Anhui Province: an indication of the establishment of the Qingyijiang River - Chun-sheng Hu; Chen-qi Hu; Shao-chen Liu; Guang-lai Xu; Li Wu; Li-hui Yang (Journal of Mountain Science, 2017)

Identification and functional analysis of the GTPV bidirectional promoter region - Hui Zhang; Zhihua Sun; Na Zhang; Zhiqiang Li; Pengyan Wang; Qiang Fu; Yan Ren; Xuehua Shao; Yu Zhang; Zhiru Guo; Chuangfu Chen (Archives of Microbiology, 2017)

Transcriptomic analysis of Casuarina equisetifolia L. in responses to cold stress - Hai-Bo Li; Nan Li; Shao-Zong Yang; Hua-Zheng Peng; Li-Ling Wang; Yong Wang; Xiao-Mian Zhang; Zhi-Hui Gao (Tree Genetics & Genomes, 2017)

Vimentin is important in the neural differentiation of PC12 cells promoted by sialylation - Li Hui Wu; Xiao Ting Shao; Jun Xia Guo; Hui Sun; Qi Chen; Jing Pan; Qian Qian Cai; Yi Wei Dong; Zhong Yi Chen; Xiao Mei Yan; Min Peng; Nanbert Zhong; et al. (Glycoconjugate Journal, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Sirtuin-3 (SIRT3) protects pancreatic β-cells from endoplasmic reticulum (ER) stress-induced apoptosis and dysfunction - Hao-Hao Zhang; Xiao-Jun Ma; Li-Na Wu; Yan-Yan Zhao; Peng-Yu Zhang; Ying-Hui Zhang; Ming-Wei Shao; Fei Liu; Fei Li; Gui-Jun Qin (Molecular and Cellular Biochemistry, 2016)

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation - Jie Song; Na Li; Yang Xia; Zhong Gao; Sa-Feng Zou; Yu-Hui Yan; Shao-Heng Li; Yue Wang; Ya-Kun Meng; Jing-Xian Yang; Ting-Guo Kang (Journal of Molecular Neuroscience, 2016)

The Kuqa late Cenozoic fold–thrust belt on the southern flank of the Tian Shan Mountains - Yue-Jun Li; Lei Wen; Hong-An Zhang; Tai-Zhu Huang; Hui-Li Li; Yuan-Yuan Shi; Qing-Long Meng; Geng-Xin Peng; Shao-Ying Huang; Qiang Zhang (International Journal of Earth Sciences, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

A research update on the potential roles of aquaporin 4 in neuroinflammation - Yu-Long Lan; Deng-Yang Fang; Jie Zhao; Tong-Hui Ma; Shao Li (Acta Neurologica Belgica, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Unexpected decrease in yield and antioxidants in vegetable at very high CO2 levels - Yuming Fu; Lingzhi Shao; Hui Liu; Hongyan Li; Zhiruo Zhao; Peiliang Ye; Pingzhen Chen; Hong Liu (Environmental Chemistry Letters, 2015)

A New Ex Vivo Method for Effective Expansion and Activation of Human Natural Killer Cells for Anti-Tumor Immunotherapy - Hui Yang; Ruihua Tang; Jing Li; Yaxiong Liu; Linjie Ye; Dongyan Shao; Mingliang Jin; Qingsheng Huang; Junling Shi (Cell Biochemistry and Biophysics, 2015)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Isolation, expression and characterization of rbcL gene from Ulva prolifera J. Agardh (Ulvophyceae, Chlorophyta) - Zhanru Shao; Wei Li; Hui Guo; Delin Duan (Journal of Ocean University of China, 2015)

NMR-Based Metabolic Profiling Reveals Neurochemical Alterations in the Brain of Rats Treated with Sorafenib - Changman Du; Xue Shao; Ruiming Zhu; Yan Li; Qian Zhao; Dengqi Fu; Hui Gu; Jueying Kong; Li Luo; Hailei Long; Pengchi Deng; Huijuan Wang; et al. (Neurotoxicity Research, 2015)

Bergapten promotes bone marrow stromal cell differentiation into osteoblasts in vitro and in vivo - Ji-jie Xiao; Wen-ji Zhao; Xin-tao Zhang; Wen-long Zhao; Xiao-xia Wang; Shu-hui Yin; Fang Jiang; Yin-xia Zhao; Fang-ni Chen; Shao-lin Li (Molecular and Cellular Biochemistry, 2015)

Differential protein expression analysis following olfactory learning in Apis cerana - Li-Zhen Zhang; Wei-Yu Yan; Zi-Long Wang; Ya-Hui Guo; Yao Yi; Shao-Wu Zhang; Zhi-Jiang Zeng (Journal of Comparative Physiology A, 2015)

Validation of a practical normalized soil moisture model with in situ measurements in humid and semi-arid regions - Dianjun Zhang; Zhao-Liang Li; Ronglin Tang; Bo-Hui Tang; Hua Wu; Jing Lu; Kun Shao (International Journal of Remote Sensing, 2015)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

Bacterial growth efficiency in a partly eutrophicated bay of South China Sea: Implication for anthropogenic impacts and potential hypoxia events - Xing-Yu Song; Hua-Xue Liu; Yu Zhong; Ye-Hui Tan; Geng Qin; Kai-Zhi Li; Ping-Ping Shen; Liang-Min Huang; You-Shao Wang (Ecotoxicology, 2015)

Inhibitory role of reactive oxygen species in the differentiation of multipotent vascular stem cells into vascular smooth muscle cells in rats: a novel aspect of traditional culture of rat aortic smooth muscle cells - Haibo Song; Hui Wang; Weiwei Wu; Lei Qi; Lei Shao; Fang Wang; Yimu Lai; Desiree Leach; Bryan Mathis; Joseph S. Janicki; Xing Li Wang; Dongqi Tang; et al. (Cell and Tissue Research, 2015)

Radiation-Induced Bystander Effects in A549 Cells Exposed to 6 MV X-rays - Shuning Yang; Jing Xu; Weixian Shao; Chong Geng; Jia Li; Feng Guo; Hui Miao; Wenbin Shen; Tao Ye; Yazhou Liu; Haiting Xu; Xuguang Zhang (Cell Biochemistry and Biophysics, 2015)

Comparative pharmacokinetics of oxytetracycline in blunt-snout bream (Megalobrama amblycephala) with single and multiple-dose oral administration - Ru-Qin Li; Yu-Wei Ren; Jing Li; Can Huang; Jun-hui Shao; Xiao-Xuan Chen; Zhi-Xin Wu (Fish Physiology and Biochemistry, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Endogenous nitric oxide in Pseudomonas fluorescens ZY2 as mediator against the combined exposure to zinc and cefradine - Yan-Bin Xu; Yan Zhou; Jing-Jing Ruan; Shi-Hui Xu; Ji-Dong Gu; Shao-Song Huang; Li Zheng; Bao-Hong Yuan; Li-Hua Wen (Ecotoxicology, 2015)

Construction of a High-Density Simple Sequence Repeat Consensus Genetic Map for Pear (Pyrus spp.) - Hui Chen; Yue Song; Lei-Ting Li; M. Awais Khan; Xiu-Gen Li; Schuyler S. Korban; Jun Wu; Shao-Ling Zhang (Plant Molecular Biology Reporter, 2015)

Mutation breeding of high 4-androstene-3,17-dione-producing Mycobacterium neoaurum ZADF-4 by atmospheric and room temperature plasma treatment - Chao Liu; Xian Zhang; Zhi-ming Rao; Ming-long Shao; Le-le Zhang; Dan Wu; Zheng-hong Xu; Hui Li (Journal of Zhejiang University-SCIENCE B, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Inhibition of the Activation and Recruitment of Microglia-Like Cells Protects Against Neomycin-Induced Ototoxicity - Shan Sun; Huiqian Yu; Hui Yu; Mei Honglin; Wenli Ni; Yanping Zhang; Luo Guo; Yingzi He; Zhen Xue; Yusu Ni; Jin Li; Yi Feng; et al. (Molecular Neurobiology, 2015)

Rapid evaluation of reference evapotranspiration in Northern China - Shao-hua Zhao; Yong-hui Yang; Feng Zhang; Xin-xin Sui; Yun-jun Yao; Na Zhao; Qiuxiao Zhao; Chun-qiang Li (Arabian Journal of Geosciences, 2015)

Isolation and molecular characterization of two novel HMW-GS genes from Chinese wheat (Triticum aestivum L.) landrace Banjiemang - Hui Shao; Tian-hong Liu; Cong-Fu Ran; Li-Qun Li; Jing Yu; Xin Gao; Xue-Jun Li (Genes & Genomics, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

Aquimarina penaei sp. nov., isolated from intestinal tract contents of Pacific white shrimp, Penaeus vannamei - Xiaoyi Li; Liping Wang; Hui Huang; Qiliang Lai; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Production of salidroside and polysaccharides in Rhodiola sachalinensis using airlift bioreactor systems - Yang Li; Chun-Hui Shao; So-Young Park; Xuan-Chun Piao; Mei-Lan Lian (Acta Physiologiae Plantarum, 2014)

Assessment of the Iodine Status of the Wa National Boarding School Students in Southwest China - Jian-Zhong Yin; Yue-Mei Feng; Shao-Xiong Wu; Xue-Hui Zhang; Song-Mei Wang; Qi Wang; Yuan Li; De-Li Qi (Biological Trace Element Research, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Universal DNA primers for amplification complete mitochondrial genome for sturgeons - Weiwei Shao; Li Wei; Linmiao Li; Hui Wang; Zhihua Lin; Jinping Chen (Conservation Genetics Resources, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Effect of temperature decrease on hemocyte apoptosis of the white shrimp Litopenaeus vannamei - Bin Li; Jian-An Xian; Hui Guo; An-Li Wang; Yu-Tao Miao; Jian-Min Ye; Chao-Xia Ye; Shao-An Liao (Aquaculture International, 2014)

ABCD2 Score May Discriminate Minor Stroke from TIA on Patient Admission - Hui Zhao; Qingjie Li; Mengru Lu; Yuan Shao; Jingwei Li; Yun Xu (Translational Stroke Research, 2014)

New briarane-type diterpenoids from gorgonian Ellisella dollfusi from the South China Sea - Yuan-Ming Zhou; Chang-Lun Shao; Hui Huang; Xiu-Li Zhang; Chang-Yun Wang (Natural Product Research, 2014)

Absorptive constituents and their metabolites in drug-containing urine samples from Wuzhishan miniature pigs orally administered with Buyang Huanwu decoction - Dong-Hui Yang; Xiang-Liang Ren; Feng Xu; Xiao-Qing Ma; Guang-Xue Liu; Cang-Hai Li; Chen Li; Shao-Qing Cai (Journal of Natural Medicines, 2014)

Antifouling Activity of Secondary Metabolites Isolated from Chinese Marine Organisms - Yong-Xin Li; Hui-Xian Wu; Ying Xu; Chang-Lun Shao; Chang-Yun Wang; Pei-Yuan Qian (Marine Biotechnology, 2013)

Functional identification of the gene encoding the enzyme involved in mannosylation in ramoplanin biosynthesis in Actinoplanes sp. - Jun-Sheng Chen; Yuan-Xi Wang; Lei Shao; Hai-Xue Pan; Ji-An Li; Hui-Min Lin; Xiao-Jing Dong; Dai-Jie Chen (Biotechnology Letters, 2013)

An AFLP, SRAP, and SSR Genetic Linkage Map and Identification of QTLs for Fruit Traits in Pear (Pyrus L.) - Rui-ping Zhang; Jun Wu; Xiu-gen Li; M. Awais Khan; Hui Chen; Schuyler S. Korban; Shao-ling Zhang (Plant Molecular Biology Reporter, 2013)

The emergence of HIV-1 primary drug resistance genotypes among treatment-naïve men who have sex with men in high-prevalence areas in China - Juan Yang; Hui Xing; Jianli Niu; Lingjie Liao; Yuhua Ruan; Xiang He; Yi Feng; Zhe Li; Yiming Shao (Archives of Virology, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

DEL RBC transfusion should be avoided in particular blood recipient in East Asia due to allosensitization and ineffectiveness - Chao-peng Shao; Bao-yan Wang; Shi-hui Ye; Wen-li Zhang; Hua Xu; Nai-bao Zhuang; Xiao-ying Wu; Heng-gui Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Cloning, Characterization and Functional Analysis of a Phenylalanine Ammonia-lyase Gene (FtPAL) from Fagopyrum tataricum Gaertn - Cheng Lei Li; Yue Chen Bai; Hui Chen; Hai Xia Zhao; Ji Rong Shao; Qi Wu (Plant Molecular Biology Reporter, 2012)

The Expression of Chicken Selenoprotein W, Selenocysteine-synthase (SecS), and Selenophosphate Synthetase-1 (SPS-1) in CHO-K1 Cells - Yan-hui Han; Zi-wei Zhang; Cheng Shao; Shu Li; Shi-wen Xu; Xiao-long Wang (Biological Trace Element Research, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Isolation of 106 Microsatellite Markers for the Pacific Abalone from a Trinucleotide-Enriched Library - Zhen Zhang; Bu-jin Xu; Li-bo Zhang; Hui Sun; Qing-guo He; Shao-wen Wang; Xiao-wen Sun; Xiao Liu (Biochemical Genetics, 2011)

Moisture sorption characteristics of freeze-dried human platelets - Meng-jie Xu; Guang-ming Chen; Ju-li Fan; Jin-hui Liu; Xian-guo Xu; Shao-zhi Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

PI3K-dependent host cell actin rearrangements are required for Cronobacter sakazakii invasion of human brain microvascular endothelial cells - Qiang Li; Wei-Dong Zhao; Ke Zhang; Wen-Gang Fang; Ying Hu; Shao-Hui Wu; Yu-Hua Chen (Medical Microbiology and Immunology, 2010)

Alleviation of ovariectomy-induced osteoporosis in rats by Panax notoginseng saponins - Yang Shen; Yong-Qi Li; Shao-Ping Li; Lin Ma; Li-Ju Ding; Hui Ji (Journal of Natural Medicines, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Mutation characteristics of the PAH gene in four nationality groups in Xinjiang of China - Wu-Zhong Yu; Dong-Hui Qiu; Fang Song; Li Liu; Shao-Ming Liu; Yu-Wei Jin; Yan-Ling Zhang; Hong-Yun Zou; Jiang He; Quan Lei; Xing-Wen Liu (Journal of Genetics, 2008)

Identification and characterization of EST-SSRs and cpSSRs in endangered Cycas hainanensis - Zheng-Feng Wang; Wan-Hui Ye; Hong-Lin Cao; Zhong-Chao Li; Shao-Lin Peng (Conservation Genetics, 2008)

Evaluation of DNA damage in Chinese toad (Bufo bufo gargarizans) after in vivo exposure to sublethal concentrations of four herbicides using the comet assay - Xiao Hui Yin; Shao Nan Li; Le Zhang; Guo Nian Zhu; Hui Sheng Zhuang (Ecotoxicology, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Expression of a truncated ripening inhibitor (RIN) protein from tomato and production of an anti-RIN antibody - Hong-Liang Zhu; Ben-Zhong Zhu; Ya-Li Zhang; Yi Shao; Xiao-Guang Wang; Yuan-Hong Xie; An-Jun Chen; Ying-Cong Li; Hui-Qin Tian; Yun-Bo Luo (Biotechnology Letters, 2007)

A new cerebroside from fruits of Ailanthus altissima Swingle - Chun-Chao Zhao; Jian-Hua Shao; Nan Wang; Xian Li; Jin-Hui Wang (Natural Product Research, 2006)

A new anthraquinone from Galium verum L. - Chun-Chao Zhao; Jian-Hua Shao; Xian Li; Jing Xu; Jin-Hui Wang (Natural Product Research, 2006)

Phylogeography and Origin of Sheep Breeds in Northern China - Yue-Hui Ma; Shao-Qi Rao; Shen-Jin Lu; Guan-Yu Hou; Wei-Jun Guan; Hong-Bin Li; Xia Li; Qian-Jun Zhao; Jun Guo (Conservation Genetics, 2006)

Status of Biological Studies and Aquaculture Development of the Mud Crab, Scylla serrata, in China: An Experimental Ecological Studies - Wang Gui-zhong; Li Shao-jing; Zeng Chao-shu; Lin Shu-jun; Kong Xiang-hui; Ai Chun-xiang; Lin Qiong-wu (Aquaculture International, 2005)

Phylogenetic diversity of Archaea in prawn farm sediment - Peng Shao; Yueqin Chen; Hui Zhou; Lianghu Qu; Ying Ma; Heyang Li; Nianzhi Jiao (Marine Biology, 2004)

Alteration of N-acetylglucosaminyltransferases in pancreatic carcinoma - Bi-cheng Nan; Dong-min Shao; Hui-li Chen; Yong Huang; Jian-xin Gu; Yi-bin Zhang; Zhao-guang Wu (Glycoconjugate Journal, 1998)